Impact of Energy Balance on Cancer Disparities - Bowen, Deborah J.; Denis, Gerald V.; Berger, Nathan A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This volume reviews disparities in cancer genetics, etiology, treatment and survivorship that are associated with differences in energy balance and how those differences and disparities may be affected by geography, socioeconomic status, ethnicity, biology, behavior and others. State-of-the-art strategies are outlined to alter these problems at the individual, community and policy levels. The book provides a comprehensive assessment of the multiple contributions of disparities in energy balance and how they affect cancer. this volume should constitute a valuable resource to disparity focused investigators at all levels and serve s an important guide to professionals that deal with these issues, especially those who determine and implement policy.
Obesity and Cancer in Appalachia -- Disparities in Cancer Outcomes A UK Perspective -- Behavioral Differences Leading to Disparities in Energy Balance and Cancer -- Impact of obesity, race, and ethnicity on cancer survivorship -- The biology of aging: Role in cancer, metabolic dysfunction and health disparities -- Energy Balance and Multiple Myeloma in African Americans -- Single Nucleotide Polymorphisms in Obesity and Inflammatory Genes in African Americans with Colorectal Cancer -- Ethnic Differences in Insulin Resistance as a mediator of Cancer Disparities -- Role of ethnic differences in mediators of energy balance -- Community-Based Strategies to Alter Energy Balance in Underserved Breast Cancer Survivors -- The role of policy in reducing inflammation -- Cancer Prevention through Policy Interventions that Alter Childhood Disparities in Energy.
Keywords: Cancer research; Metabolism; Medicine; Cancer Research; Metabolomics; Medicine/Public Health, general; Biomedicine, general